The Impact of Economic Conditions on Traditional and new Categories of Property Crimes – An Exploratory Research in European Countries – - Bartoletti, Silvia (Mediterranean Journal of Social Sciences, 2012)
The goal of this paper is to evaluate at a macro level the link that exists between different types of property crimes(theft, burglary, fraud, offences against the computer) and economic indicators in the 27 countries of the European Union.Crimes selected belong to ‘old’ and ‘new’ categories of property crimes. They are collected from the ‘the European Sourcebookof crime and criminal Justice statistics’ while the economic indicators are collected from two European surveys, EU-SILC andLFS. Variables related to the population structure (‘age’ and ‘gender’) are added in the analysis. Statistical techniques(correlation and multiple regression analysis) will be useful to build a framework of indicators which contributes to a betterunderstanding of the interactions between criminality and economic indicators. A parameterized model, function of the mainfactors of crime, will help to understand old and new categories of property crime and their potential directions in Europe.